Pengaruh Penggunaan Metode Kreatif dalam Pembelajaran Keislaman pada Anak Usia Dini - Nurul Saputri (Jurnal Al Athfaal, 2023)
Islamic education for early childhood plays a crucial role in shaping their character and religious identity. This research aims to investigate the influence of using creative methods in Islamic education for young children. In this study, we conducted a series of learning activities involving various creative methods, such as role-playing, arts, and interactive storytelling. Our research method involved a group of young children divided into two groups. The first group received traditional instruction, while the second group received education using creative methods. We measured the development of Islamic understanding, interest, and motivation in children in their engagement with Islamic teachings. The research findings indicate that the group receiving education with creative methods demonstrated a significant improvement in their understanding of Islam, interest, and motivation compared to the group receiving traditional instruction. This suggests that creative methods can help young children better comprehend Islamic teachings, enhance their interest in Islam, and motivate them to learn more. The results underscore the importance of using creative methods in Islamic education for early childhood. Pedagogical implications from this research emphasize the need for innovative approaches in teaching religious principles to children. These findings can serve as a foundation for the development of more effective and engaging Islamic education curricula for young children.